EFFECTS PRICE, TRANSPORTATION SERVICES AND OPERATIONAL PERFORMANCE ON SATISFACTION THROUGH QUALITY OF PASSENGER SERVICE BUS TRANS BATAM, INDONESIA - Irwansyah Irwansyah; Chablullah Wibisono; Gadis Baru; Ika Novitasari (Ensiklopedia of Journal, 2019)
The purpose of this study is to know how the effect of Price, Service Transportation and Operational Performance Against Satisfaction Through Quality Passenger Bus Service Trans Batam, and to determine the effect of prices, Transport Services and Operational Performance directly to passenger satisfaction Bus Trans Batam. The research method used is descriptive quantitative that is giving explanation about the description of Price Effect, Transport Service And Operational Performance To Satisfaction Through Quality Passenger Bus Service Trans Batam. Primary data were collected from respondents or questionnaires distributed and analyzed in which the tool has been tested before being used to collect data, and the results of each instrument are valid and reliable. Data analysis technique used Structural Equetion Model (SEM) analysis. The population in this study amounted to 187 people are the users of the car trans Batam. The result of research that the variable of Price, Transportation Service, Operational Performance, Service Quality and Satisfaction, have influence equal to 73,80% to Satisfaction, and influence equal to 64,40% to Service Quality. Square Multiple Correlation value for Square Multiple Correlation variable whose value respectively for Satisfaction R2 = 0, 738 is identical with R2 on SPSS of 0, 738 then the magnitude of Determination is Square Multiple Correlation value for Satisfaction variable 100% = 0, 738 x 100% = 73.80%. Thus it can be stated that the change in Satisfaction is influenced by the price of 73.80%. For Service Quality R2 = 0.644 then the magnitude of Determination = 0.644 x 100% = 64.40%.